An effective length model for octet lattice. (May 2018) - Chen, X.Y.; Tan, H.F.
Highlights: Develop a satisfying theoretical model for predicting the relative compressive stiffness and strength of octet lattice material with cylindrical struts for large aspect ratio ranges. The relative compressive stiffness and strength not only depend on the relative density, but also relate to the effect of strut joint, bend and shear. The material overlapping effect in strut joint and the coupling effect between the shearing force and the bending moment will raise the relative compressive stiffness and strength. At low relative density, the strut joint effect is the dominating factor in stiffness analytical derivations. As the relative density increase, the importance of the bending and shearing effect are more obvious. Abstract: As technology advance in 3D printing, octet lattice materials can be made with a wide range of strut aspect ratios. It is essential to develop a satisfying theoretical model for large aspect ratio ranges. In this paper, an analytical model considering material overlapping effect in strut joint, bend and shear has been derived to predict the effect compressive stiffness and strength of the octet lattice materials with cylindrical struts. The models have been validated by FE simulations and experiments. These results demonstrate that the relative compressive stiffness and strength not only depend on the relative density, but also relate to the effect of strut joint, bend and shear. The material overlapping effect in strut joint and the coupling effect between the shearing force and the bending moment will raise the relative compressive stiffness and strength. Graphical abstract: Image, graphical abstract